2008
DOI: 10.2353/ajpath.2008.070640
|View full text |Cite
|
Sign up to set email alerts
|

Severe Intrauterine Growth Restriction Pregnancies Have Increased Placental Endoglin Levels

Abstract: Endoglin, a co-receptor for transforming growth factor (TGF)-␤ 1 and -␤ 3 is expressed in the human placenta and plays an important role in the pathogenesis of preeclampsia. Because preeclampsia is associated with hypoxia, and because TGF-␤3 is overexpressed in preeclamptic pregnancies, we examined the effect of oxygen and TGF-␤3 on placental endoglin expression and investigated its expression in pathological models of placental hypoxia such as intrauterine growth restriction (IUGR) pregnancies. Endoglin expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 42 publications
3
71
0
6
Order By: Relevance
“…Oxygen will also regulate the placental expression of endoglin via TGF-beta3. Reduced placental perfusion leading to placental hypoxia might contribute to the increased expression of endoglin (Yinon et al, 2008). In our study, we found that the increased sENG levels in normal twin amniotic fluids, which compared with normal singletons.…”
Section: Figuresupporting
confidence: 57%
“…Oxygen will also regulate the placental expression of endoglin via TGF-beta3. Reduced placental perfusion leading to placental hypoxia might contribute to the increased expression of endoglin (Yinon et al, 2008). In our study, we found that the increased sENG levels in normal twin amniotic fluids, which compared with normal singletons.…”
Section: Figuresupporting
confidence: 57%
“…Levine et al (11) demonstrated higher circulating endoglin in women with SGA neonates. Yinon et al (12) have shown that placental endoglin mRNA concentration were higher in severely growth restricted infants. Jeyebalan et al (13) noted that maternal circulating endoglin concentrations were not higher in growth restricted babies compared to uncomplicated pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…These finding suggest that endoglin levels may responsible for the pathogenesis of PE and/or IUGR. 17 Increase in soluble endoglin may, in turn, create an anti-angiogenic milieu in the circulation and lead to the maternal manifestations of preeclampsia. The effect of gestational age at delivery on the differences in level is not known and further studies are required in this aspect to explore whether primary pathology is uteroplacental response to fetal placental vasculature or uterine circulation constraints on placenta and foetus.…”
Section: Discussionmentioning
confidence: 99%